Near-infrared electrochemiluminescence in water through regioselective sulfonation of diaza [4] and [6]helicene dyes. Issue 68 (30th July 2020) - Li, Haidong; Duwald, Romain; Pascal, Simon; Voci, Silvia; Besnard, Céline; Bosson, Johann; Bouffier, Laurent; Lacour, Jérôme; Sojic, Neso
Abstract : A series of water-soluble helicene dyes generating intense electrochemiluminescence (ECL) signal in physiological conditions is reported. Abstract : A series of water-soluble helicene dyes generating intense electrochemiluminescence (ECL) signal in physiological conditions is reported. Those species were prepared using diaza [4] and [6]helicenes as structural cores modified with sulfonate groups in various positions. Such groups improve their water solubility and can induce a red-shifted emission. Efficient ECL up to the near-infrared is achieved in water, demonstrating a viable strategy for the design of new near-infrared ECL dyes for bioassays and microscopy.